K-Graceful, Odd-Even Graceful, Heronian Mean and Analytic Mean Labeling for the Extended Duplicate Graph of Kite Graph - Anitha, K.; Selvam, B.; Thirusangu, K. (International Journal of Engineering and Technology, 2018)
In this paper, we investigate the extended duplicate  graph of  kite graph KI3,m admits K-graceful, Odd-Even graceful, Heronian mean and Analytic mean labeling.